The Impact of Oil Prices on the Capital Expenditures of the State Budget in Azerbaijan - Ahmadov, Baghish (International Journal of Energy Economics and Policy, 2022)
The article studies the theoretical and practical approaches related to the allocation of oil revenues for public investment. Based on the two-step Engel-Granger procedure for cointegration analysis, the relationship between the ratio of the capital expenditures of the state budget to non-oil GDP and the logarithm of real oil prices in Azerbaijan is investigated. It has been determined that public investment in Azerbaijan is highly dependent on the oil price, and the volatility of the oil price also affects the volatility of these expenditures. So, it was proposed that the capital expenditures of the state budget should be determined based on the goals of economic development, and not depending on changes in oil prices.